Development and validation of an immune prognostic signature for ovarian carcinoma. Issue 4 (19th February 2019) - Khadirnaikar, Seema; Kumar, Pranjal; Shukla, Sudhanshu Kumar
Abstract: Background: Ovarian cancer (OC) causes a significant proportion of cancer‐related deaths in women. Recently, immunotherapy has emerged as a substantial player in cancer treatment. Lymphocyte infiltration, an important indicator of immune activity and disease aggressiveness, can be identified by gene expression profiling of immune‐related genes of tumours which may prove useful in prognosis of patients. Aims: The aim of this study is to identify and validate a novel immune gene‐based prognostic signature for OC. Methods and results: Here, we extracted the expression of immune‐related genes and performed the Cox regression analysis and identified five genes with significant correlation with survival in training cohort of patients (n = 286). We utilised regression coefficient and expression level of five genes to calculate immune prognostic signature (IPS) score for OC patients. In univariate and multivariate Cox regression analysis with other clinicopathological factors, we showed that IPS is an independent predictor of survival ( P value <0.01). More importantly, we utilised 404 patients from TCGA dataset as the validation cohort and validated the survival capability of IPS in the univariate and multivariate analysis ( P value <0.001). Interestingly, KM analysis showed a significant difference in survival of patients with high and low IPS score in both datasets (training dataset P value <0.01, validation dataset P value <0.01). Further, we showed that all the five genes are differentially expressed and involved in immune modulation among other pathways. Interestingly, GSEA analysis showed that high IPS patients had low immune activity and activated EMT and other oncogenic pathways. Conclusion: In summary, we have developed and validated robust immune‐related gene‐based prognostic signature to identify the OC patients with high immune activity who can be taken for immunotherapy.